The Use of Executable FIT Tables to support Maintenance and Evolution Tasks - Ricca, Filippo; Torchiano, Marco; Di Penta, Massimiliano; Ceccato, Mariano; Tonella, Paolo (Electronic Communications of the EASST, 2008)
Acceptance testing is a kind of testing performed prior to software delivery.In the agile approach, acceptance test suites are specified by analysts and customers during the requirement elicitation phase and used to support the development/maintenance activities. This paper reports an experiment with master students that investigates on the usefulness of executable acceptance test cases, developed by using FIT (Framework for Integrated Test), during software maintenance andevolution activities. The preliminary results indicate that FIT tables help students to correctly perform the maintenance/evolution tasks with no significant impact on time.